Environmental governance and the emergence of forest-based social movements - Cronkleton, P.; Taylor, P.L.; Barry, D.M.; Stone-Jovicich, S.; Schmink, M. (Center for International Forestry Research, 2008)
This occasional paper is based on the results of a three-year project examining the emergence of forest-based grassroots movements in Latin America. Funded by the Ford Foundation, the Support to Grassroots Community Forestry Organizations in Central America and Brazil Project sought to understand how grassroots groups develop and influence conservation and development. The project focused on four noteworthy cases in Central America and Brazil, each representing ‘successful’ broad-based collective action to defend local control and use of forest lands. Cases included the Association of Forest Communities of the Petén in Guatemala, the Siuna Farmerto-Farmer exchange programme in Nicaragua, the Mamirauá Sustainable Development Reserve in the Brazilian state of Amazonas, and the Brazilian rubber tapper movement in Acre. Although the context and outcomes varied, in these cases grassroots collective action to defend local livelihoods emerged when initially weak government institutions attempted to counteract chaotic frontier conditions through the imposition of conservation and development initiatives, provoking local resistance. A combination of indigenous capacity for collective organization and significant external assistance helped produce grassroots forest movements capable of becoming proactive partners in the management and defence of protected areas. These groups still confront external incursions into their hard-won resources rights and strive to respond to changing membership needs. The cases suggest that local communities can become effective forest stewards when acquired rights are duly recognized, avenues exist for meaningful participation, costs and benefits are distributed fairly, and appropriate external support is provided.